Prevalence of suicide over a decade in Nepal - Gurung, Minani; Tiwari, Bhuwaneshwar; Adhikari, Bikram; Maharjan, Ashmita; Nepal, Sujita; Poudel, Lisasha; Rajbhandari, Bibek; Chitrakar, Shasank (International Journal Of Community Medicine And Public Health, 2025)
Background: When developing suicide prevention strategies and programs, accurate data on suicide deaths, method and its pattern is crucial. There is still a lack of information on the techniques used and their variance across the nations. This study described the pattern of suicidal deaths and the suicide rates in Nepal. Methods: We conducted a review of records of suicide data in Nepal from 2009 to 2020 to determine the pattern of suicidal deaths in Nepal. This study includes a sample size of 42,136 suicidal deaths. For statistical analysis, R software version 4.0 was used. Parametric numerical variables were presented with mean and standard deviation, whereas categorical variables were presented as frequency and percentage. Results: From April 2009 to March 2020, a total of 42,136 suicidal deaths were recorded in Nepal. The mean age of suicide victims was 43.4 years, and the majority were male (45.7%). The average yearly suicide rate in Nepal was found to be 14.8 per 100,000 people. Hanging (69.5%) was the common method and depression (31.1%), becoming the leading causes of suicide. Suicidal attempts were found to be highest in the morning (58.4%) from 5 a.m. to 12 p.m. Conclusions: The average rate of suicide was high in comparison with other countries in Southeast Asia. The increase in the rate was mostly after a major geographical, economic, political, or health disaster. Given the importance of policies in determining a country's progress, it's time to consider suicide as a "sleeping pandemic.